PENGARUH CORPORATE SOCIAL RESPONSIBILITY BERBASISKAN KARAKTERISTIK SOCIAL BANK TERHADAP KINERJA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Putranto, Yohanes Andri; Kewal, Suramaya Suci (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2014)
The purpose of this study is to test empirically the effect of Corporate SocialResponsibility (CSR) on the financial performance of banking companies listed in the Indonesia Stock Exchange (IDX). In contrast to previous studies, this study uses the social bank characteristics for the measurement of CSR. Social bank characteristics are a proxy of sustainability development. The company's performance is proxied by Tobin's Q. The sample was banking companies listed on the IDX in 2008 to 2012. This study used a multiple regression model and the R software to test the hypothesis. At the 5% significance level, the results show that CSR significantly affects the financialÃ‚Â performance of banking companies listed in the IDX. The regression coefficient of CSRÃ‚Â on corporate performance is -0.075769, thus CSR as measured by the social bank characteristics as a proxy of sustainability development is significantly negative on firm financial performance as measured by Tobin's Q. In other words, CSR-basedsustainability development does not affect the increase of financial performance of banking companies that are listed in the IDX.